2022
DOI: 10.1021/acsami.2c13742
|View full text |Cite
|
Sign up to set email alerts
|

Intriguing H2S Tolerance of the PtRu Alloy for Hydrogen Oxidation Catalysis in PEMFCs: Weakened Pt–S Binding with Slower Adsorption Kinetics

Abstract: High quality of hydrogen is the key to the long lifetime of proton-exchange membrane fuel cell (PEMFC) vehicles, while trace H2S impurities in hydrogen significantly affect their durability and fuel expense. Herein, we demonstrate a robust PtRu alloy catalyst with an intriguing H2S tolerance as the PEMFC anode, showing a stronger antipoisoning capability toward hydrogen oxidation reaction compared with the Pt/C anode. The PtRu/C-based single PEMFC shows approximately 14.3% loss of cell voltage after 3 h operat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…It should be noted that Pt–Ru/C has superior H 2 S tolerance than Pt/C and Ni/C, which is due to its slower adsorption kinetics towards S 2− species. 38 With PtRu/C, the polarization curve with H 2 S (1000 ppm H 2 S) exhibited a peak power density of nearly 25 mW cm −2 at a peak current density of nearly 70 mA cm −2 (Fig. 4(b)) which is lower than the performance metrics with pure H 2 fuel (Fig.…”
Section: Resultsmentioning
confidence: 84%
See 1 more Smart Citation
“…It should be noted that Pt–Ru/C has superior H 2 S tolerance than Pt/C and Ni/C, which is due to its slower adsorption kinetics towards S 2− species. 38 With PtRu/C, the polarization curve with H 2 S (1000 ppm H 2 S) exhibited a peak power density of nearly 25 mW cm −2 at a peak current density of nearly 70 mA cm −2 (Fig. 4(b)) which is lower than the performance metrics with pure H 2 fuel (Fig.…”
Section: Resultsmentioning
confidence: 84%
“…This decay in performance can be attributed to slow poisoning of the platinum electrode by sulphur-containing species. 38 In situ electrochemical mass spectrometry during spontaneous fuel purification of the H 2 -H 2 S mixture (1000 ppm H 2 S) shows the consumption of H 2 in the anodic half-cell (red trace in Fig. 4(d)) and the generation of pure H 2 streams in the cathodic half-cell (green trace Fig.…”
Section: Spontaneous Fuel Purification Of Binary Mixtures Containing ...mentioning
confidence: 99%
“…S1E, ESI †), readily assigned to Au 4f 7/2 and Au 4f 5/2 of Au 0 from PdPtAu alloys. Considering the high binding affinity between noble metals and thiol groups (e.g., binding energy of 161.8/162.8/162.6 eV for Pd/Pt/Au-S [29][30][31] ), the as-prepared trimetallic alloys showed potential in directly extracting biological thiols from complex clinical biosamples.…”
Section: Construction and Characterization Of Pdptau Alloysmentioning
confidence: 99%
“…For molecular structure, PdPtAu alloys demonstrated preference targeting thiol-containing molecules, especially biothiols, because of the synergistic affinity resulting from the Au-S bond (binding energy of B162.6 eV) and Pt-S bond (binding energy of B162.8 eV) between PdPtAu alloys and biothiols. 30,31 Notably, the adsorption rate (see the detailed calculation in the detection preference determination) of Cys as measured by LDI MS detection was as high as 13.15 AE 0.87%, by using PdPtAu alloys as both the affinity probe and enhancement matrix (Table S1, ESI †). This adsorption rate was comparable or even better than the value reported in previous literature.…”
Section: Preference Analysis Of Pdptau Alloysmentioning
confidence: 99%
“…Modeling results have shown that normalPnormalt-Sads ${{\rm P}{\rm t}-{{\rm S}}_{ads}}$ formed on the catalyst surface can be oxidized to SO3 ${{{\rm S}{\rm O}}_{3}}$ or SO42- ${{{\rm S}{\rm O}}_{4}^{2-}}$ consuming water, leading to decreased membrane conductivity and S crossover to the cathode, negatively affecting the oxygen reduction reaction and diminishing the PEMFC performance [29,30] . Therefore, efforts have been made to develop PtRu, [31–33] PtCo, [34,35] and PtNi [36,37] alloy catalysts with high resistance to CO and H 2 S to mitigate these poisoning effects. Extensive studies have been conducted on the effects and mechanisms of poisoning caused by CO and H 2 S individually.…”
Section: Introductionmentioning
confidence: 99%